PENGARUH FINANCIAL SATISFACTION DAN FINANCIAL KNOWLEDGE TERHADAP FINANCIAL BEHAVIOR DENGAN LOCUS OF CONTROL SEBAGAI VARIABEL INTERVENING SAAT TERJADI WABAH COVID-19 PADA PEGAWAI PT. JASA TIRTA ENERG - Eko Santoso; Arisyahidin; Eka Askafi (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
The purpose of this study was to determine the effect of Financial Satisfaction andFinancial Knowledge on Financial Behavior with Locus of Control as anintervening variable. The population of this research is the employees of PT. JasaTirta Energi has 108 employees and a sample of 85 employees is calculated basedon the slovin formula. This study uses a quantitative approach with data collectionmethods using a questionnaire. Data analysis techniques using descriptiveanalysis and inferential analysis with the help of Smart PLS program. Based onthe results of the study it can be concluded that; (1) financial satisfaction has aninfluence on the locus of control, (2) financial knowledge has an influence on thelocus of control, (3) financial satisfaction has no effect on financial behavior, (4)financial knowledge has no influence on financial behavior, (5) locus of controlhas an influence on financial behavior, (6) financial satisfaction indirectly directlyaffect financial behavior through locus of control as an intervening variable, (7)financial knowledge indirectly affects financial behavior through locus of controlas an intervening variable.